Role of Personnel Management in TISCO - Dr. VIJAY PRAKASH (International journal of economic perspectives, 2022)
The Personnel Management in TISCO is continued to be harmonious for the last ninety years . The country has witnessed many occurrences of the Industrial disturbances in the different industries in last 85 years , whereas TISCO has been proved to be an ideal model of the Industrial harmony . The Personnel Management in TISCO is based on the Founder’s Philosophy propounded by Jamshed Ji Naserwanje Tata . The sound relations between the management and the union is the experience of such a long period of co - operation . The Founder , J.N. Tata’s philosophy stated that the company should consider socio - economic aspects of all sections of the people , besides producing the steel . The basic guidelines of the functions of personnel and the Personnel Management in TISCO is efficient as the managers of the organisation always consider basic philosophy of the Founder’s as their function guide . The Personnel Management in the organisation became more strong after the chairmanship of Mr. J.R.D. Tata who lead the company in the marvelous manner . Once he stated that to achieve the efficient working conditions to provide higher wages and good emenities to the employees , the good Personnel Management programme should be launched in the company . He stated that the better relations between the management and labour should be maintained . Such a better relationship could be obtained only by creating a sense of trust and confidence to each other . He further stated that the sense of rust and the confidence can be established if the labourers are considered most important Personality in the industry and their feelings and sentiments should also be recognised and given due regard . The Articles of Association of the company has also lay down some important objectives of the organisation to maintain better Industrial Relations in the organization.